2000
DOI: 10.1104/pp.122.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Border Cell Production in Response to Increased Carbon Dioxide Levels

Abstract: Field soil atmospheres have higher CO 2 and lower O 2 concentrations compared with ambient atmosphere, but little is known about the impact of such conditions on root exudation patterns. We used altered levels of CO 2 and O 2 relative to ambient conditions to examine the influence of the atmosphere on the production of root border cells by pea (Pisum sativum) root tips. During germination, atmospheres with high CO 2 and low O 2 inhibited root development and border cell separation in pea seedlings. Later in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…Hawes (1990) and Zhao et al (2000) found, the RBC in some plant species such as pea (P. sativum) and other legumina species could be observed and collected from the root as about 5 mm in length, but not from shorter roots. And the maximum RBC number got its maximum (about 4,000) when the root was 25 mm in length.…”
Section: Discussionmentioning
confidence: 95%
“…Hawes (1990) and Zhao et al (2000) found, the RBC in some plant species such as pea (P. sativum) and other legumina species could be observed and collected from the root as about 5 mm in length, but not from shorter roots. And the maximum RBC number got its maximum (about 4,000) when the root was 25 mm in length.…”
Section: Discussionmentioning
confidence: 95%
“…If root cap turnover under all conditions were constitutively active, as was long presumed, then defining the cellular sources, nature and quantity of root exudation from this source, at least, would be straightforward because this material is easily harvested and analysed. However, the process of cap turnover actually is regulated in a species-dependent manner in response to endogenous and environmental signals (reviewed in Hawes and Brigham, 1992;Hawes et al, 2000Hawes et al, , 2003. As a result, release of border cells and their associated products is variable; like microbial colonization patterns, their presence along the root as it grows forms a variable and discontinuous pattern (Brigham et al, 1997;Mosse, 1976).…”
Section: Discussionmentioning
confidence: 96%
“…The controlled delivery of this complex mixture of products from the root occurs in parallel with root cap turnover, which is regulated in a speciesdependent manner by endogenous and environmental signals Clowes, 1978;Hawes and Lin, 1990;Hawes et al, 1998;Ijima et al, 2000;Miyasaka and Hawes, 2000;Woo et al, 1999;Zhao et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, reports that roots from plants grown aeroponically are capable of turning off the process of border cell separation suggest that culture conditions may affect differentiation of border cells from the root cap (Hawes and Lin, 1990;Hawes and Brigham, 1992;Stephenson and Hawes, 1994). Indeed, recently Zhao et al (2000) showed that increased CO 2 levels increased the number of border cells in roots.…”
Section: Introductionmentioning
confidence: 93%